Cervical Cancer Screening With Human Papillomavirus DNA and Cytology in Japan. Issue 3 (1st March 2017) - Sasaki, Yuri; Iwanari, Osamu; Arakawa, Ichiro; Moriya, Takuya; Mikami, Yoshiki; Iihara, Kuniko; Konno, Ryo
Abstract : Objective: The aim of this study was to determine the value of human papillomavirus (HPV) testing for primary cervical cancer screening in Japan. Methods: In total, 5065 women who underwent primary screening with cytology and HPV between January 2005 and December 2006 were enrolled. In the baseline phase, these women were stratified by age, and the rates of HPV-positive and abnormal cytology were compared between women younger than and older than 30 years. In the follow-up phase, women aged 20 to 69 years and cytology negative for intraepithelial lesions or malignancy at baseline were followed up until December 2011 (n = 2383). Progression to grade 2/3 cervical intraepithelial neoplasia or worse (CIN2+/CIN3+) was compared between the HPV-positive and HPV-negative groups. Results: In the baseline phase, HPV-positive rates were significantly higher in women younger than 30 years at 20.7% (95% confidence interval [CI], 18.4–22.9; 255/1234) compared with women 30 years or older at 7.2% (95% CI, 6.4%–8.0%; 275/3831; P < 0.001). However, there was no statistical difference for high-grade squamous intraepithelial lesion or worse rates between them, at 2.7% (95% CI, 1.8%–3.6%; 33/1234) and 2.4% (95% CI, 1.9%–2.9%; 91/3831), respectively, P = 0.55. In the follow-up phase, the rate of progression to CIN2+/CIN3+ was significantly higher in the HPV-positive group than in the HPV-negative group ( P < 0.001). Moreover, relative risk of progression to CIN2+ was 15.9 times higher in the HPV-positive group, and that of progression to CIN3+ was 16.1 times higher in the HPV-positive group. Conclusions: Human papillomavirus testing is a useful test for predicting progression to CIN and is recommended as a primary screening tool. However, screening with cytology alone is still appropriate for younger women, younger than 30 years, because HPV testing yields more false-positive results in younger women.